Implementation Of Sgd's Program Of A Mall In Indonesia In Increasing Awareness Of Ev Friendly Practice - Baeng, Rucita Theola; Octafyanti, Lia; Aruan, Alexander Mamby (Peneliti.net, 2025)
Plaza Indonesia, a prominent shopping center in Jakarta, Indonesia, aims to enhance environmental consciousness among millennials. This research delves into the campaign's effectiveness in attracting millennial participation and fostering environmental stewardship. A mixed-methods approach was employed to assess the campaign's impact. Quantitative data was gathered through surveys administered to millennial mall visitors, while qualitative data was obtained through in-depth interviews with campaign organizers and millennial participants. The campaign's success can be attributed to its creative and engaging approach, which resonated with millennials. The use of social media, influencer marketing, and experiential activities effectively captured millennial attention and encouraged participation. Plaza Indonesia's environmental awareness campaign serves as a successful model for engaging millennials in environmental initiatives. The campaign's creative approach and focus on experiential engagement provides valuable insights for other organizations seeking to connect with this demographic